Clotting-Factor Concentrations 5 Days After Discontinuation of Warfarin. Issue 6 (August 2018) - Benzon, Honorio T.; Asher, Yogen; Kendall, Mark C.; Vida, Loyda; McCarthy, Robert J.; Green, David
Abstract : Background: The American Society of Regional Anesthesia and Pain Medicine guidelines recommend discontinuation of warfarin and an international normalized ratio (INR) of 1.2 or less before a neuraxial injection. The European and Scandinavian guidelines accept an INR of 1.4 or less. We evaluated INR and levels of clotting factors (CFs) II, VII, IX, and X 5 days after discontinuation of warfarin. Methods: Patients who discontinued warfarin for 5 days and had an INR of 1.4 or less had activities of factors II, VII, IX, and X measured. The primary outcome was the frequency of subjects with CF activities of less than 40%. Results: Twenty-three patients were studied; 21 (91%) had an INR of 1.2 or less. In these 21 patients, the median (interquartile range) activities of factors II, VII, IX, and X were 66% (52%–80%), 114% (95%–132%), 101% (84%–121%), and 55% (46%–63%), respectively. Ninety-five percent (99% confidence interval, 69%–99%) had CF activities of greater than 40%. The patient who did not CF activities greater than 40% had end-stage renal disease. Two subjects had an INR of greater than 1.2; the activities of factor II, VII, IX, and X were 37% and 46%, 89% and 105%, 66% and 78%, and 20% and 36%, respectively. Neither patient had CF activities of greater than 40%. Conclusions: Based on 40% activity of CFs, patients with INRs of 1.2 or less can be considered to have adequate CFs to undergo neuraxial injections. The number of patients with an INR of 1.3 and 1.4 is too small to make conclusions.